Influência do eucalipto na produção de milho em sistema de integração lavoura-floresta, no cerrado de Roraima - Silva, Marcos Wanderley da (2015)
The rotation of annual cultures with pasturage and trees has been utilized as one of the alternatives for the economic and ecological sustainability of systems of agricultural production, with corn being one of the principle annual cultivations using the iPLF system, due principally to the tradition of cultivation, to the great number of commercial cultivation types adapted to the different regions of Brazil. The present work had as its objective the evaluation of interference of eucalyptus thinning and of the planting distance on the agronomic performance of corn in the iLF system, after the fifth and sixth years of cultivation, in the Roraima Savannah. The experiment was conducted in experimental unit in the 2013 and 2014 agricultural years, on the Água Boa/Embrapa experimental grounds, Boa Vista Municipality, RR. The experimental delimitation was done in blocks, in this instance, with the model of subdivided parcels, with (D) thinning, being the principle variable, with 3 levels (D0: without thinning, D1, thinning on the first line of eucalyptus and D2: thinning of two lines of eucalyptus) and as a second variable (d) the distance, with 9 levels (2.5; 5.0; 7.5; 10.0; 12.5; 15.0; 17.5; 20.0 and 22.5m) placed in rows with three repetitions, totaling 81 experimental units. The characteristics of the corn were evaluated, height of the plant, number of ears, plant dry mass, grain productivity and mass of 1000 grains. As well as chemical characteristics of pH, P, K, Ca2+, Mg2+, Al3, organic material and solid humidity.. The minimum distance of planting corn in relation to eucalyptus with 5 and 6 years old in ILF system in Roraima savannah is 17 m. The spatial arrangement of eucalyptus x corn influence the levels of pH , Ca 2+ , Mg 2+ , P and MO the Soil. Thinning of 1 and 2 rows eucalyptus favor the phosphorus content in the layer between 10 and 30 cm depth and the soil organic matter in layers 5-10 and 10-30 cm deep. Higher pH values, K and Mg 2+ occur in the layer 0-5 cm. O eucalyptus in Crop- forest integration system provided less development of corn plants as well as lower values of the components of grain yield.